Suitability Analysis for the Locations of Schools Using Geographic Information System (GIS) and Remote Sensing for Al-Diwaniyah City, Iraq - M. Al-khuzaie, Marwah; Janna, Hussein; A. Al-Yousify, Hayder; Al-Rubaye, Ahmed (International Journal of Engineering and Technology, 2018)
There are several factors affect the determination of the best location for schools, however, it is very difficult to satisfy by one method for location determination. These factors can be classified to environmental, economic, technical and political social demands. In this study, a frame work, depended on analytic hierarchy process, for determination of the best location an ArcGIS10.1 software was applied to deal with geographical information system and uncertainty situations. Nine sets were used in this study: distance from emergency facilities, distance from existing schools, distance from roads, distance from rivers, distance from railway, distance from land use, distance from gas pipe and population density. Four scores then were found depending on normalizing of the nine sets: Unsuitable, Less Suitable, Suitable and Most Suitable areas. This research aims to find the best locations for primary schools by creating a model which applied into construction and making digital maps and hard copy for the schools that can be updated with demanded. Using GIS will make a huge development in selecting the locations of new schools and also can be applied in different other sectors.Â Â